Gymnasium Classicum Petropolitanum - Zeltchenko, Vsevolod (Hyperboreus, 2014)
The paper presents an overview of the history of St Petersburg Grammar school (school no. 610). Since its foundation in 1989 it remains the only state-funded school with obligatory study of both ancient languages in Russia. The author discusses the aims and principles of the school and analyses its program of Greek and Latin in comparison to the Classical schools of modern Europe and in prerevolutionary Russia.